Mourning mothers and wars that never end: reading Nasim Marashi’s Haras (Pruning) in the shadow of the Iran-Iraq war - Moosavi, Amir (Taylor and Francis, 2025)
The Iran-Iraq War (1980–1988), which the Iranian government frames as a ‘Sacred Defense’, occupies a large space in contemporary Persian fiction, sometimes in surprising ways. This article focuses on the 2017 novel Haras (Pruning) by Nasim Marashi (Nasīm Marʿashī), which despite being shaped entirely by the context of the Iran-Iraq War rarely treats the experience of living through it. The article explores how Haras builds on previous works that use the war not as a focal point, like conventional war literature, but a point of departure to explore different stories about post-war Iran, intricately connected to, yet far beyond, the war with Iraq. The article postulates that by using the war with Iraq to call attention to the loss of people, homes, and the environment, Haras uses the war to innovatively challenge the messaging of the Islamic Republic.